Rotações óticas CAM-B3LYP em comprimentos de onda diferentes: comparação com resultados CCSD - Oliveira, Amanda Ziviani de (2015)
A hierarchical sequence of basis sets along with one long-range corrected functional (CAMB3LYP) are used to calculate electronic optical rotations at three wavelengths (355.0, 589.3, and 633.0 nm) of fourteen rigid chiral molecules whose experimental values are available in the literature. As the results show to be sensitive to the basis set quality, complete basis set limits are estimated. Special attention is given to five particularly difficult compounds. In these cases, one verifies that vibrational corrections must be added to the CAM-B3LYP equilibrium optical rotations to correct signs. In general, the complete basis set limits reported in this work are in good agreement with the experimental data and with those obtained at a higher level of theory. For some compounds, solvent effects are taken into account.